Influence of normal stress on the shear strength of the structural plane considering the size effect - Huang, Yuxi; Hu, Gaojian (Frontiers in Earth Science, 2023)
The shear strength of a structural plane is a critical parameter in the analysis of engineering rock stability. Significant differences exist due to the various normal stresses in the structural plane. Therefore, evaluating the rock deformation to effectively determine the influence of normal stresses at different scales on the shear strength of structural planes is of great significance. This study discusses the effects of normal stress and structural plane size on shear strength through numerical simulations and regression analysis. The results showed that the shear strength of the structural plane increases linearly with increasing normal stress. The shear strength of the structural plane decreases with increasing size, and the corresponding curve is exponential. The characteristic size and shear strength increase linearly with increasing normal stress. This paper presents the concrete form of these relationships, which can be used to calculate and predict the shear strength, which has significance in guiding engineering.